Pengaruh Gaya Mengajar Guru Terhadap Hasil Belajar Siswa Kelas XI IPS Pada Mata Pelajaran Sosiologi Di SMA Katolik St. Albertus Malang - Grace Jauhari; I Gusti Ngurah Agung Krisna Aditya; Wahyu Budi Nugroho (Saskara : Indonesian Journal of Society Studies, 2026)
SMA Katolik St. Albertus Malang continuously develops an adaptive learning system that accommodates generational differences among students, particularly through the application of diverse teaching styles. This study aims to determine the influence of teachers’ teaching styles on the learning outcomes of Grade XI Social Science students in Sociology during the 2024/2025 academic year. A quantitative approach was employed, using questionnaires, observations, and documentation as data collection techniques. The analysis was based on six teaching style indicators: voice variation, focusing, eye contact, pausing, body movement and facial expression, and teacher mobility. The results show that the teachers’ teaching styles were generally in the “fairly good” category, with dominant aspects including voice variation, eye contact, and pausing, which effectively enhanced students’ motivation and understanding. Statistical analysis confirmed a significant positive relationship between teachers’ teaching styles and students’ learning outcomes, highlighting the importance of adaptive and continuously developed teaching approaches in effective learning outcomes.